2022
DOI: 10.1186/s12967-022-03811-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Malate Ringer's solution on myocardial injury in sepsis and enforcement effects of TPP@PAMAM-MR

Abstract: Background Myocardial dysfunction played a vital role in organ damage after sepsis. Fluid resuscitation was the essential treatment in which Lactate Ringer's solution (LR) was commonly used. Since LR easily led to hyperlactatemia, its resuscitation effect was limited. Malate Ringer's solution (MR) was a new resuscitation crystal liquid. Whether MR had a protective effect on myocardial injury in sepsis and the relevant mechanism need to be studied. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“… 29 It’s reported that Malate Ringer’s fluid reduced myocardial injury in septic rats by improving mitochondrial function and inhibiting apoptosis, with L-malate playing a crucial role. 13 Our TPP@PAMAM encapsulating L-malate to form RPP@PAMAM@MA was confirmed in preliminary studies to target myocardial mitochondria, reducing consumption and delivering more L-malate to myocardial mitochondria, providing more raw materials for ATP synthesis.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“… 29 It’s reported that Malate Ringer’s fluid reduced myocardial injury in septic rats by improving mitochondrial function and inhibiting apoptosis, with L-malate playing a crucial role. 13 Our TPP@PAMAM encapsulating L-malate to form RPP@PAMAM@MA was confirmed in preliminary studies to target myocardial mitochondria, reducing consumption and delivering more L-malate to myocardial mitochondria, providing more raw materials for ATP synthesis.…”
Section: Discussionmentioning
confidence: 58%
“… 12 Our previous study indicated that TPP-MR significantly protected against myocardial injury in sepsis. 13 However, it remained unclear whether TPP-MR offered protection against myocardial injury in hemorrhagic shock.…”
Section: Introductionmentioning
confidence: 99%
“…The room maintained a temperature of 23-25°C and a relative humidity of 40%-70%. The rat sepsis model was established through cecal ligation and puncture (CLP) according to a previous study 24 - 25 . After 12 hours of CLP, the rats were sacrificed, and their hearts were collected for further research.…”
Section: Methodsmentioning
confidence: 99%